2014
DOI: 10.1053/j.gastro.2013.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Carcinomas With CpG Island Methylator Phenotype 1 Frequently Contain Mutations in Chromatin Regulators

Abstract: BACKGROUND & AIMS Subgroups of colorectal carcinomas (CRCs) characterized by DNA methylation anomalies are termed CpG island methylator phenotype (CIMP)1, CIMP2, or CIMP-negative. The pathogenesis of CIMP1 colorectal carcinomas, and their effects on patients’ prognoses and responses to treatment, differ from those of other CRCs. We sought to identify genetic somatic alterations associated with CIMP1 CRCs. METHODS We examined genomic DNA samples from 100 primary CRCs, 10 adenomas, and adjacent normal-appearin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 30 publications
4
67
1
Order By: Relevance
“…Interestingly, CHD8 alterations also have been described as somatic events in gastric, colorectal, skin, and glioblastoma multiforme cancers (11)(12)(13)(14). Despite its evident importance, little is known from previous studies about the cellular and molecular consequences of disrupting a single copy of CHD8 and the regulatory connection between this chromatin-remodeling enzyme and the critical pathways associated with either neurodevelopment or cancer.…”
Section: −10mentioning
confidence: 99%
“…Interestingly, CHD8 alterations also have been described as somatic events in gastric, colorectal, skin, and glioblastoma multiforme cancers (11)(12)(13)(14). Despite its evident importance, little is known from previous studies about the cellular and molecular consequences of disrupting a single copy of CHD8 and the regulatory connection between this chromatin-remodeling enzyme and the critical pathways associated with either neurodevelopment or cancer.…”
Section: −10mentioning
confidence: 99%
“…A single mutation has been reported in RNF20 in colorectal cancer cells (Barber et al 2008). A recent study of CpG island methylator phenotype 1 (CIMP1)-associated colorectal tumours has shown an enrichment of mutations in genes encoding proteins associated with chromatin remodelling, including a low frequency of mutations in RNF20 and RNF40 (Tahara et al 2014). The effect of hypermethylation, or mutations, on RNF20 protein levels was not investigated in these studies; however, the implication is that these events probably lead to less active RNF20 capable of functioning to monoubiquitinate histone H2B.…”
Section: H2bub1 and Associated Machinery In Primary Tumoursmentioning
confidence: 99%
“…49 In this series, CIMP1 (high level CIMP) was classified based on a panel of 7 markers. A classification of CIMP1 required hypermethylation of the MLH1 gene promoter, as well as 4/6 of the remaining markers.…”
Section: Discussionmentioning
confidence: 99%